Health Education from An Early Age: Implementation and Evaluation of Healthy School Technical Guidance (Bimtek) in Early Childhood Education Institutions in Kediri Regency - Anik Lestariningrum; Intan Prastihastari Wijaya; Nur Lailiyah; Isfauzi Hadi Nugroho; Sagista Cahayanti; Marselina Ngindang; Wika Nadya Belvana; Kheiza Reva Maharafni (CV Media Inti Teknologi, 2026)
Background: Education on clean and healthy living habits from an early age is an important foundation for developing children’s character and future health quality. However, the implementation of healthy school programs in early childhood education (PAUD) institutions still faces various challenges, including limited educator understanding and the suboptimal management of healthy learning environments. Objectives: This article aims to describe the implementation and evaluate the effectiveness of healthy school technical guidance (BIMTEK) activities for PAUD educators. Methods: The study employed a qualitative descriptive method with a participatory approach through the stages of planning, implementation, and evaluation of the BIMTEK activities. The participants consisted of PAUD teachers and administrators who were actively involved in the training program under the supervision of the Education Office of Kediri Regency. Data collection techniques included observation, interviews, and documentation. Results: The results showed that the healthy school BIMTEK activities improved educators’ understanding and skills in implementing healthy school principles, including sanitation management, environmental cleanliness, and the habituation of clean and healthy living behaviors (PHBS) among children. In addition, positive changes were identified in learning practices that became more integrated with health values. The evaluation also indicated an increased institutional commitment to creating healthy and child-friendly PAUD environments. Conclusion: Therefore, the healthy school BIMTEK program was considered effective as a strategic effort to support the sustainable implementation of healthy school programs in PAUD institutions.